2017
DOI: 10.1186/s12866-017-1141-0
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of HepP: a virulence-related Pseudomonas aeruginosa heparinase

Abstract: Background Pseudomonas aeruginosa is an opportunistic pathogen that causes serious infections in immunocompromised hosts including severely burned patients. In burn patients, P. aeruginosa infection often leads to septic shock and death. Despite numerous studies, the influence of severe thermal injuries on the pathogenesis of P. aeruginosa during systemic infection is not known. Through RNA-seq analysis, we recently showed that the growth of P. aeruginosa strain UCBPP-PA14 (PA14) in whole blood obtained from s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 82 publications
(138 reference statements)
0
3
1
Order By: Relevance
“…donghuensis HYS killed worms in 5 days, and the average LT 50 value was 3.25 ± 0.15 days (n = 3). This virulence is stronger than that of PA14 or PAO1 previously reported 17,18 . Repellence of worms by P .…”
Section: Resultscontrasting
confidence: 60%
“…donghuensis HYS killed worms in 5 days, and the average LT 50 value was 3.25 ± 0.15 days (n = 3). This virulence is stronger than that of PA14 or PAO1 previously reported 17,18 . Repellence of worms by P .…”
Section: Resultscontrasting
confidence: 60%
“…HPA expression was increased in animal models of septic lung and kidney injury, suggesting that HPA may be involved in the early onset of sepsis (66). An additional study demonstrated that expression of the gene coding for HPA (hepP) plays an important role in a mouse model of sepsis induced by Pseudomonas aeruginosa, and that mutations in the hepP gene enhance survival in infected mice (67)(68)(69). A previous in vivo study determined that patients with sepsis induced by gram-negative bacteria exhibited a pronounced increase in plasma HPA activity (70).…”
Section: Hpa In Sepsismentioning
confidence: 99%
“…Pseudomonas , a genus of obligate aerobic Gram-negative bacilli, belongs to the class of Gammaproteobacteria [ 3 , 4 , 5 , 6 ]. This genus contains many pathogen species, including P. aeruginosa , P. putida , P. fluorescens and P. syringae [ 7 , 8 , 9 ]. P. donghuensis exhibits antifungal and plant-promoting activities [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%